2017
DOI: 10.1002/2016ja023127
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of 17–18 March 2015 geomagnetic storm on the Indian longitudes using GPS and C/NOFS

Abstract: The largest geomagnetic storm in solar cycle 24 occurred during 17–18 March 2015 where the main phase of the storm commenced from 07:00 UT of 17 March 2015 and reached the Dst negative minimum at 22:00 UT. The present paper reports observations of total electron content (TEC), amplitude, and phase scintillations from different GPS stations of India during the storm of 17 March and highlights its effects on GPS. It also presents the global equatorial spread F (ESF) occurrence during the storm using total ion de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Patra et al [] ascribed the plasma bubbles and irregularities to the rapid uplift of the ionosphere, which caused strong postsunset scintillations in a very narrow longitudinal zone in India. Ray et al [] showed during the March 2015 storm a significant TEC enhancement during the day and intense phase scintillation at night. Spogli et al [] indicated that PPEF could suppress in a statistical sense the occurrence of equatorial plasma bubbles and scintillation during geomagnetically disturbed days.…”
Section: Main Results: Geospace Responses To the St Patrick's Day Stmentioning
confidence: 99%
“…Patra et al [] ascribed the plasma bubbles and irregularities to the rapid uplift of the ionosphere, which caused strong postsunset scintillations in a very narrow longitudinal zone in India. Ray et al [] showed during the March 2015 storm a significant TEC enhancement during the day and intense phase scintillation at night. Spogli et al [] indicated that PPEF could suppress in a statistical sense the occurrence of equatorial plasma bubbles and scintillation during geomagnetically disturbed days.…”
Section: Main Results: Geospace Responses To the St Patrick's Day Stmentioning
confidence: 99%
“…It should also be noted that the positive storm effect observed for the CME-induced storm on October 13-14 was less significant than that observed during the CIR-induced storm on October 16-17. This is due to the fact that the onset of the storm at 23:00 UT on October 12 was not in the local (LT= UT+05:30) morning to noon sector in which the ionization production mechanism dominates and plasma accumulation due to mechanical effec t of neutral wind is greater than its chemical loss due to recombination (Prolss, 1991;Balan et al, 2010;Ray et al, 2017).…”
Section: Storms Of October 12-20 2016mentioning
confidence: 99%
“…Global ionospheric effects of the geomagnetic storm on 17 March 2015 have emerged as the most extensively studied magnetic storm effects in recent years (Carter et al, ; Huang et al, ; Jiang et al, ; Kakad et al, ; Kil et al, ; Kuai et al, ; Nava et al, ; Nayak et al, ; Ramsingh et al, ; Ray et al, ; Tulasi Ram et al, ; Zhou et al, ). As has been recorded in several of the above references, and shown here in Figure a, on 17 March 2015, following a sudden storm commencement triggered at about 04:45 UT, the SYM‐H index started decreasing when the z‐component of the interplanetary magnetic field (IMF) turned southward at ~6 UT, indicating the onset of the magnetic storm.…”
Section: Ionosonde and Geomagnetic Observations At Equatorial Stationmentioning
confidence: 99%